Atypical presentation of cerebral schistosomiasis four years after exposure to Schistosoma mansoni - Matthew F. Rose; Eli E. Zimmerman; Liangge Hsu; Alexandra J. Golby; Emam Saleh; Rebecca D. Folkerth; Sandro S. Santagata; Danny A. Milner Jr.; Shakti H. Ramkissoon (Epilepsy and Behavior Case Reports, 2014)
Schistosomiasis is the second most socioeconomically devastating parasitic disease worldwide, affecting over 240 million people in 77 countries on 5 continents and killing 300,000 people annually in sub-Saharan Africa alone. Neuroschistosomiasis is caused by granuloma formation around eggs that lodge in the CNS, with Schistosoma mansoni and Schistosoma haematobium usually affecting the spinal cord and Schistosoma japonicum causing most reported cerebral disease. We report a case of a previously healthy 25-year-old woman native to the United States who presented with a single generalized tonic–clonic seizure without other neurologic symptoms four years after spending a semester in Ghana where she went swimming once in a river. Brain MRI showed areas of signal abnormality and mottled nodular linear enhancement in the left temporal and right posterior temporal/parietal lobes and right cerebellum without mass effect. A biopsy of the left temporal lesion showed prominent granulomas with dense mixed inflammatory infiltrates composed of eosinophils, plasma cells, and lymphocytes surrounding refractile egg shells containing characteristic embryonal cells and von Lichtenberg's envelope and displaying the pathognomonic spine shape of S. mansoni. Serum ELISA and antibody immunoblots confirmed exposure to S. mansoni. In summary, we describe the atypical combination of cerebral schistosomiasis due to S. mansoni, after a prolonged interval of four years, from a single known exposure.